Pengaruh Penambahan Kinesiotaping Setelah Senam Hamil Untuk Mengurangi Nyeri Punggung Bawah Pada Ibu Hamil - SHABRINA, ANNA, Wahyuni.S.Fis.,SKM.,M.Kes (2016)
Background: during the pregnancy happened many changes on the body so that there arose some sense of discomfort, aches and pains. Back pain is a nuisance that many experienced by pregnant women. Not only occur on particular trimester, but experienced throughout pregnancy until the pscanatal period. Research objectives: to know the influence of addition of kinesiotaping after gymnastics pregnant to reduce lower back pain in pregnant women. The benefits of research: be aware of the influence of the addition of kinesiotaping after gymnastics pregnant to reduce lower back paint in pregnant women.Research method: this type of research was quasi experimental approaches with experiment and design research pre and post test two group design. Sample retrieval techniques in Purposive Sampling. The number of 14 samples of pregnant women. Result of research: there is the influence of the addition of kinesiotaping after gymnastics pregnant after a test done wilcoxon retrieved value Asymp. SIG (2-tailed) Group of 0,018 = while pregnant gymnstics retrieved value Asymp. SIG (2 - tailed) of 0.018 = Mann Whitney test obtained value to decrease pain press Asymp results. SIG (2 - tailed) < 0.05 ) which means there is a difference between the influence of calisthenics gymnastics after Kinesiotaping pregnant and pregnant. Conclusin: there is the influence of the addition of Kinesiotaping after gymnastics pregnant to reduce lower back pain in pregnant womwn.